A Need Analysis of ESP materials for Agriculture Students at Indonesian Vocational School in West Sulawesi - Ibnu Hajar; Anita Triastuti (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
The development of industry in the modern era has led to the growth of vocational schools in Indonesia. for that reason, vocational schools need to adapt or change the general English (GE) learning materials into English learning materials for specific purposes (ESP). therefore, this current study aims to investigate the need for ESP materials for agriculture students at Indonesian vocational schools. This study employed descriptive research to describe the agriculture students’ need for ESP materials. The participants of this research were 25 students of XI grade agriculture students at vocational school. This research used a questionnaire that was developed to find out the ESP needs of agriculture students. Moreover, the data from the questionnaire were analyzed by seeing the frequency of participants’ answers then the data were presented in the form of a chart or figure. The results of the study showed that the English learning objective of the agriculture students should make the students able to communicate in English well. Then, English learning materials for agriculture students should be blended with the agriculture materials such as cultivation plants and processing agricultural products. Also, English learning activities for agriculture students should involve students actively by group work, making projects, and using current media technologies in the learning process. Eventually, the results of this study can be used as a reference in mapping and developing ESP materials especially for agriculture students at vocational schools.